Securing Southeast Asian Regional Security: Indonesia Diaspora - Hendra Manurung (Proceeding Of The International Seminar and Conference on Global Issues, 2015)
Following the lead of Chinese Diaspora, Indonesia has now started looking at the strength of Indonesian descent is spread throughout the world. When India and China began to rise economically on the global stage, one of the first things both nations did was to tap into their global diaspora. The millions of Chinese and Indians living on foreign soil and had achieved success responded by channeling billions of dollars back to their homeland as well as providing expertise. With the first Indonesian Diaspora Congress scheduled to open in Los Angeles on July 7, 2012, Indonesia, too, is beginning to recognize the power of those who have moved abroad. Speaking on the eve of the opening of the three-day congress, Indonesian Ambassador to the United States Dino Patti Djalal said that so far Indonesians abroad had been largely ignored. But the congress, which already has registered participants from several other countries, will be a major step toward ensuring that Indonesians living abroad will continue to have a bond with their homeland. As the ambassador noted, the congress can build friendship and a spirit of togetherness between Indonesian diaspora groups. The government also hopes that the congress will awaken a new sense of awareness among the diaspora to create synergy with Indonesians back home. Therefore the congress can boost greater economic and social links between Indonesia and the world. Indonesians living abroad can be a bridge linking the country to other nations and the global economic grid. This is vital in a globalized world and will give Indonesia an extra edge. The Indonesian diaspora can play a significant role in the continued growth and development of the country. Given that many of them have built successful careers and lives in distant lands, they can form an extended network of brain power and source of capital for the nation and strengthen our second track diplomacy in the global stage. Keywords: indonesian diaspora, globalization, global economics, national identity, brain power, capital